Originality, Imitation, and Plagiarism: Teaching Writing in the Age of the Internet - Martha Vicinuseauthor; Caroline Eisner (University of Michigan Press, 2008)
This collection is a timely intervention in national debates about what constitutes original or plagiarized writing in the digital age. Somewhat ironically, the Internet makes it both easier to copy and easier to detect copying. The essays in this volume explore the complex issues of originality, imitation, and plagiarism, particularly as they concern students, scholars, professional writers, and readers, while also addressing a range of related issues, including copyright conventions and the ownership of original work, the appropriate dissemination of innovative ideas, and the authority and role of the writer/author. Throughout these essays, the contributors grapple with their desire to encourage and maintain free access to copyrighted material for noncommercial purposes while also respecting the reasonable desires of authors to maintain control over their own work. Both novice and experienced teachers of writing will learn from the contributors' practical suggestions about how to fashion unique assignments, teach about proper attribution, and increase students' involvement in their own writing. This is an anthology for anyone interested in how scholars and students can navigate the sea of intellectual information that characterizes the digital/information age.